Circumlocutory Imperialism: Watan in the Thoughts of Syed Shaykh bin Ahmad al-Hady - Alatas, Ismail F. (Studia Islamika, 2005)
This article seeks to examine such transition. Specifically, it focuses on the concept of watan(Ar. Watan or homeland) in the view of an early 20th century Muslim modernist, Syed Shaikh bin Ahmad al-Hady. Watan - as proclaimed by al-Hady - had a modern and secular connotation, posing a challenge to the prevalent worldview of the Malays and kerajaan(kingdom). The conceptualization of watan was new for most Malays. Identity was constructed predominantly in relation to the particular state in which a person resided. The significance of al-Hady's contribution was that he conceptualized watan in the sense of patrie which consequently became the pivotal basis for the construction of a modern nation-state.DOI: 10.15408/sdi.v12i2.590